Guidance Note for Adaptive Management - Ministry of Foreign Affairs of Denmark (Government of Denmark, 2022)
This note explains what adaptive aid management is; why and when it should be considered; and how it should be applied. It covers all Danish development support channels and modalities, including bilateral country assistance, assistance to and through civil society, the private sector and to and through multilateral organisations. This guide has three chapters. Chapter 1 provides an executive overview of what adaptive management is. Chapter 2 goes deeper into five key operational principles of adaptive management. Chapter 3 details the main tenets of adaptive management processes during the programming cycle.

Guidance Note: Practical introduction to adaptive management - DT Global (DT Global, 2022)
DT Global is proud to introduce our new Guidance Note: Practical Introduction to Adaptive Management There is a growing consensus around adaptive management as an effective (even necessary) approach when programs are tackling complex development problems. While there is no standard definition of adaptive management, there is general agreement that such programs need to routinely engage with and respond to program context; constantly test what works in that context; and adjust approaches, plans, and activities based on continuous learning. However, there remains a more limited body of evidence about what this looks like in practice—the enabling conditions, systems, resourcing, skills, and attitudes to effectively operationalise adaptive management. There is also limited guidance around when adaptive management is required, and to what extent—both critical and often overlooked considerations when planning for successful adaptive management. This Guidance Note draws together lessons and good practice in adaptive management from across DT Global’s diverse portfolio of donor-funded programs. It outlines our conceptual framework for adaptive management, with practical guidance on how it can be applied by our program teams. It is also designed to help our teams distinguish adaptive management from good (non adaptive) project management, consider when adaptive management is most useful on a program, and how adaptive a program (or part of a program) should be.

Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in international development practice for over a decade. Learning-by-doing is a crucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporating data collection processes that generate useful, timely and practical information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in Mozambique. MUVA, we suggest, is atypically evidence-led. It combines systematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring, evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, how MEL systems are designed to prioritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of funders.This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclude by considering the relevance, or not, of MUVA’s approach to programmes in other contexts or issue areas trying to replicate a similarly evidence-informed approach to adaptive management. Key messages Learning-by-doing is essential to adaptive programming, but it can be challenging to establish data collection processes that generate useful, timely and practical information. MUVA – a female economic empowerment programme in Mozambique – has an atypically evidence-led adaptive management approach. This has two fundamental features. One, data collection and analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of implementing staff than to the reporting requirements of funders. Monitoring, evaluation and learning (MEL) systems are designed to prioritise actionable learning. This approach was enabled by building collective ownership over the programme’s objectives and the purpose of MEL from the outset. Implementers are asked about their motivations, and these are related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and through structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (CLARISSA Research and Evidence Paper, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.

Study on application of Adaptive Management (AM) in Education Out Loud (EOL) project implementation in the Horn, Eastern adn Southern Africa (HESA) - ANHRE (Oxfam, 2022)
This study mainly aimed to look at adaptive management in the program cycle (throughout Program Cycle processes, including strategy, project, and activity design and implementation) and to look at the Enabling Conditions: how an organization’s culture, business processes, and resource allocation support adaptive management. It explores elements of adaptive management that correspond to the objectives of the study as follows: 1) Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology. 2) Examine how adaptive management has been applied in EOL project implementation thus far. 3) Explore ways in which an adaptive management approach can be used as a source of learning during project implementation. 4) Propose ways in which the application of adaptive management can be improved in EOL project implementation. Objective 1: Assess grantees’ level of understanding of adaptive management as a programming approach and a method of risk mitigation Methodology: The researchers asessed whether the EOL program, GMU, and HESA RMU have a culture of openness, continuous learning, reflection, and improvement. This assessment looked at actual practices and perceptions of field-based staff and project officers. In addition, they looked at processes to assess knowledge management and decision-making process – the ability to distill, share and disseminate knowledge and the awareness among grantees/ employees of the decision-making process. Summary of findings: Understanding of adaptive management as a programming approach among the selected sample of grantees was linked to continuous learning, the ability to adjust implementation and inform decision making to reach the intended objectives based on analysis and assessment of the context and flexibility in management. RMU HESA was perceived to have a culture of openness where grantees feel comfortable sharing their opinion and ideas and is perceived to be receptive to proposed changes to projects and encourage grantees to provide feedback. The HESA RMU-Oxfam Denmark is also seen as an agency that is very “flexible“. Recommendations: Enhance Capacity building on adaptive management tools, particularly for finance and admin teams with a focus on pro-active adaptive management which scans the horizon for opportunities and risks, and it adapts to take advantage of them. It explicitly plans for experimentation and regular upgrading of the strategies; it considers learning and the reduction of uncertainty and imperfect knowledge as one of the key objectives of the management effort. Objective 2: Examine how adaptive management has been applied in EOL project implementation thus far Methodology: Two elements were assessed : Collaboration and how internal and external collaboration of grantees and grant agent, assessing the ability to collaborate with other departments within the entity, the ability to collaborate with learning partners, other grantees, to what extent they consult their stakeholders and their ability to build coalitions. In addition, researchers looked at Adaptation and the best practices and lessons learned in adopting change in the design, implementation, budgeting or monitoring of EOL programs and the process followed to adapt the desired change. Summary of findings: Adaptive management practices are seen to be adapting to context changes, constant learning, and flexibility. The management and coordination of EOL program is deemed to be collaborative, adaptive, and understanding of the emerging needs of EOL Program implementation. There is a simple process in place for grantees to make changes to the program implementation. Most grantees do take the time to pause and reflect on what is going well and what could be improved and to share the knowledge gained with their coalition members and regional coalitions. HESA RMU was found to be encouraging learning practices through organizing periodic online and offline regional learning and reflection workshops. Compared to other donors, the majority of grantees believe that EOL provided the highest level of flexibility and ability to adapt which is seen to be a necessity for advocacy work. However, it is important to enforce structure to tighten the feedback loop between data and action: adaptive management aims for double learning more than just correcting deviations in planned versus actual. Recommendations: Introducing outcome harvesting tool as one of the mechanisms to capture outcomes, institutionalization of adaptive management further by developing context analysis tools/ regular reviews of TOC. Further use of Scenario planning as a tool to map and plan different scenarios on how change may happen, and to examine the program’s role in making future events happen, enforcing structure to tighten the feedback loop between data and action. In addition to the introduction of quarterly planning cycles where data and information gathered in the previous quarter can be used to inform the next planning cycle and update the TOC, project design and activity implementation strategies. Objective 3: To explore ways in which an adaptive management approach can be used as a source of learning during project implementation Methodology: The team assessed the grantees’ ability to use evidence to build their pathways for change, their ability to use learning to inform decision making, the frequency and habit of reviewing their theory of change, the risks and opportunities through scenario planning, how they assess the efficiency of their data collection tools and monitoring and evaluation data quality, on whether they have a mechanism to monitor unintended outcomes (outcome harvesting) and reflect. Summary of findings: This study revealed that there is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program has adopted Re-active Adaptive Management that relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. Recommendations: Encouraging further engagement on knowledge sharing hubs and investing in knowledge transfer on adaptive management and learning to other partners in targeted countries (EOL to become an influencer in this field), encouraging further engagement from learning partners to provide mentorship and support during implementation and continuous learning on adaptive management tools. RISP and GISP could be further engaged in the monitoring process. Based on the stated objective, what was assessed and findings, it would also be interesting to enable grantees distill learnings from AM practices and applying that knowledge to improve project implementation. This means AM will be expected to go beyond changing implementation strategies and budgets and document learnings from such changes and apply them to improve the remaining part of the project. Objective 4: Propose ways in which the application of adaptive management can be improved in EOL project implementation Summary of findings: Grantees were able to articulate well their understanding of adaptive management but were less able to provide concrete examples of how adaptive management is implemented in practice. There is a culture of collaborating, learning and openness among grantees and HESA RMU. The EOL program relies on regular monitoring and reflection activities to detect unpredicted challenges and, when needed, to adjust planned actions to remain on track to achieve the desired program outcomes. EOL provided learning opportunities, platforms for knowledge sharing and encouraged peer learning among grantees. However, it is important to enforce structure to tighten the feedback loop between data and action and to institutionalize practicing adaptive management. Recommendations: A roadmap that looks at reviewing seven steps for improving adaptive management is recommended as a systematic tool to introduce improvement. This roadmap is useful in a multi-organizational, multi-country set-up where efficient design is needed to align top-down structuring and requirements with bottom-up diversity and divergence. This roadmap of seven steps is introduced by HIVOS. These 7 steps can come in a different order and it depends on the user to assess which of the seven steps needs to be undertaken. 1. Annual Review results/ outcome statements: using outcome harvesting to continuously monitor intended/ unintended outcomes (whether positive or negative or within the sphere of control (outputs) or within the sphere of influence (outcomes). 2. Learning questions: Learning from the monitoring data; Learning about the critical Make-or-Break assumptions in the Theory of Change; and Developing learning topics/ questions and learning agenda at each level 3. Changes in context: Identifying possible trends and signs about emerging shifts in the environment, followed by analyzing and collective sense-making of possible implications for the Theory of Change (is there a need to revise intervention strategies, desired outcomes, pathways, assumptions? 4. Theory of change: Reviewing the theory of change was not seen as a frequently recommended practice. Constant validation of pathways to change and evidence in the TOC is important. 5. Capacity assessment and development: What capacities are available amongst the alliance members and partner organizations in relation to the (revised) Theory of Change; What would be Capacity Development needs in view of the capacity assessment results? 6. Strategies and interventions: With the outcomes achieved and learning so far, what can you say about your interventions and strategies? What worked? Why? Is there a need for adjustment? 7. Annual reflection and Planning Who should take part in the annual planning and reflection?

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Context-monitoring for adaptive management - Pickwick, Sarah (World Vision, 2022)

Collaborating, Learning, and Adapting Framework & Key Concepts (Implementing Partner Version 1) - USAID LEARN (USAID, 2022)
Although collaborating, learning, and adapting (CLA) are not new to USAID and its implementing partners, they often do not happen regularly or systematically and are not intentionally resourced. The CLA Framework above identifies components and subcomponents to help you think more deliberately about what approach to CLA might be best tailored to your organizational or project context. The framework recognizes the diversity of what CLA can look like in various organizations and projects while also giving CLA structure, clarity, and coherence across two key dimensions: - CLA in the Program Cycle: how CLA is incorporated into planning and design processes throughout the Program Cycle in order to improve their effectiveness; and - Enabling Conditions: how an organization’s culture, daily operating processes, and resource allocation support CLA integration. Organizations need both integrated CLA practices appropriate for their context and conducive enabling conditions to become stronger learning organizations capable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the principle that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development and improve aid effectiveness.

Transforming M&E for Uncertain and Complex Contexts: The UNDP’s Innovation Sandbox Approach - Fraser, Dugan; Haldrup, Søren (Powered by Evidence Podcast, 2022)
How can we transform monitoring and evaluation (M&E) into a more adaptive, emergent process to address uncertainty and complexity in todays’ world? How do we move from compliance and accountability to learning – to support better, more timely, decisions? Join GEI Program Manager, Dugan Fraser, as he discusses these questions and others with Special Guest, Søren Haldrup, from UNDP's Strategic Innovation Unit where he manages UNDP's innovation facility and leads a new initiative called the M&E Sandbox.

Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press Publication, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.